JENIS SATWA BURUNG PADA KOMUNITAS MANGROVE DI TELUK HITU KABUPATEN MALUKU TENGAH - Sasole, Aldi; Badaruddin, Ernywati; Kaya, Manuel (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to determine the types of bird species in the mangrove area in Hitu Bay, Central Maluku Regency. The method used in this research is descriptive using direct and indirect census techniques to determine the type and distribution of birds. The results of the research show that in Hitu Bay there are 17 species of birds, consisting of 12 species of terrestrial birds and 5 species of seabirds. The bird distribution value with the lowest frequency is 0.1 and the lowest relative frequency is 1.03, namely the Common turtledove (Streptopelia chinensis), while the highest frequency is 0.9 and the highest relative frequency is 9.27, namely the Cow swallow (Collocalia esculenta), Little egret (Egretta garzetta), and Cucak kutilang (Pycnonotus aurigaster).